2008
DOI: 10.1016/j.cmet.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 Ion Channels Are Required for Sustained Phosphoinositide 3-Kinase Signaling in Lymphocytes

Abstract: Summary Lymphocytes lacking the TRPM7 dual function ion channel/protein kinase exhibit a unique phenotype: they are unable to proliferate in regular media, but proliferate normally in media supplemented with 10–15 mM extracellular Mg2+. Here, we have analyzed the molecular mechanisms underlying this phenotype. We find that upon transition from proliferation-supporting Mg2+-supplemented media to regular media, TRPM7-deficient cells rapidly downregulate their rate of growth, resulting in a secondary arrest in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 20 publications
5
105
1
1
Order By: Relevance
“…1 Similar DNA content and size parameters are observed in primary lymphocytes positioned in quiescence/G 0 , 4,5 suggesting the potential involvement of TRPM7 in processes required to transition out of quiescence/G 0 . In this study, we examined the biological events that occur when TRPM7-deficient lymphocytes are proliferation-arrested in standard tissue culture media and observed that these cells exhibit multiple signatures associated with quiescence.…”
Section: Trpm7 Regulates Quiescent/proliferative Metabolic Transitionmentioning
confidence: 48%
See 1 more Smart Citation
“…1 Similar DNA content and size parameters are observed in primary lymphocytes positioned in quiescence/G 0 , 4,5 suggesting the potential involvement of TRPM7 in processes required to transition out of quiescence/G 0 . In this study, we examined the biological events that occur when TRPM7-deficient lymphocytes are proliferation-arrested in standard tissue culture media and observed that these cells exhibit multiple signatures associated with quiescence.…”
Section: Trpm7 Regulates Quiescent/proliferative Metabolic Transitionmentioning
confidence: 48%
“…The dual function ion channel-protein kinase-transient receptor potential cation channel, subfamily M, member 7 (TRPM7) has recently been shown to support sustained phosphoinositide 3-kinase (PI3K) signaling in proliferating lymphocytes, 1 positioning TRPM7 alongside PI3K as an important component in the processes which control lymphocyte metabolism. TRPM7's influence on lymphocyte metabolism is linked to its role in regulation of cellular Mg 2+ uptake: TRPM7-deficient cells downregulate PI3K/Akt/mTOR signaling and undergo proliferative arrest when transitioned to standard tissue culture media; this phenotype is suppressible either by provision of supplemental extracellular Mg 2+ or heterologous expression of a Mg 2+ transporter.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not surprising that cell metabolism and many enzymatic activities are affected by Mg 2ϩ homeostasis (10). Mg 2ϩ deficiency results in small cell size and cell cycle arrest (11), as well as accelerated cell senescence (12), and intracellular Mg 2ϩ levels modulate the activity of many ion channels (13)(14)(15)(16)(17)(18). In whole animals, hypomagnesemia results in hypocalcemia (19,20), and Mg 2ϩ deficiency has been correlated to hypertension (21,22).…”
Section: Magnesium (Mgmentioning
confidence: 99%
“…TRPM7 has been suggested to have a central role in cellular Mg 2+ homeostasis (Schmitz et al, 2003), in central nervous system ischemic injury (Aarts et al, 2003), in skeletogenesis in zebrafish (Elizondo et al, 2005), in the defecation rhythm in Caenorhabditis elegans (Vriens et al, 2004), in cholinergic vesicle fusion with the plasma membrane (Brauchi et al, 2008), in phosphoinositide-3-kinase signaling in lymphocytes (Sahni et al, 2008), in cell death in gastric cancer (Kim et al, 2008), in osteoblast proliferation (Abed et al, 2009) and in breast cancer cell proliferation (Guilbert et al, 2009). But, until now, the effect of the 5-LOX inhibitors, NDGA, AA861 and MK886 on these TRPM7 several physiological functions have not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%